2015
DOI: 10.7554/elife.10453
|View full text |Cite
|
Sign up to set email alerts
|

Oviductal estrogen receptor α signaling prevents protease-mediated embryo death

Abstract: Development of uterine endometrial receptivity for implantation is orchestrated by cyclic steroid hormone-mediated signals. It is unknown if these signals are necessary for oviduct function in supporting fertilization and preimplantation development. Here we show that conditional knockout (cKO) mice lacking estrogen receptor α (ERα) in oviduct and uterine epithelial cells have impaired fertilization due to a dramatic reduction in sperm migration. In addition, all successfully fertilized eggs die before the 2-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 60 publications
(72 reference statements)
3
65
0
1
Order By: Relevance
“…Finally, it is also important to consider how ZP hardening influences further embryo development. It has already been reported that insufficient hardening leads to early embryonic loss (Gahlay et al, 2010; Winuthayanon et al, 2015), but whether there are any consequences of excessive hardening, especially in relation to embryo hatching, remains unclear. By creating a situation that is structurally very different from that of oocytes with an abnormally thicker ZP, a feature that does not appear to impair hatching (Syrkasheva et al, 2017), super‐hardening of the egg coat could potentially have a significant effect on the success rate of assisted reproduction in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is also important to consider how ZP hardening influences further embryo development. It has already been reported that insufficient hardening leads to early embryonic loss (Gahlay et al, 2010; Winuthayanon et al, 2015), but whether there are any consequences of excessive hardening, especially in relation to embryo hatching, remains unclear. By creating a situation that is structurally very different from that of oocytes with an abnormally thicker ZP, a feature that does not appear to impair hatching (Syrkasheva et al, 2017), super‐hardening of the egg coat could potentially have a significant effect on the success rate of assisted reproduction in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different knockout mouse models showed that impairment of ZP2 cleavage reduces fertility only partially, indicating that ZP2 processing is not essential to ensure monospermic fertilization and further successful development (Burkart et al, 2012; Gahlay et al, 2010; Rankin et al, 2003; Sachdev et al, 2012). The subfertility of these genetically modified female mice is likely to be caused by precocious ZP hatching and early embryonic loss (Burkart et al, 2012; Floehr, Dietzel, Schmitz, Chappell, & Jahnen‐Dechent, 2017; Winuthayanon et al, 2015) and there is no evidence of abnormal sperm accumulation in the perivitelline space of their oocytes (Gahlay et al, 2010; Rankin et al, 2003; Tokuhiro & Dean, 2018). The latter observation suggests the existence of a ZP2‐independent block to sperm penetration, which appears to depend on ovastacin's enzymatic activity based on the presence of supernumerary sperm in the perivitelline space of ovastacin‐deficient oocytes, as well as oocytes expressing ovastacin with an active‐site mutation (Tokuhiro & Dean, 2018).…”
Section: Cg Exocytosis Modifies the Zp After Fertilizationmentioning
confidence: 99%
“…Loss of ESR1 in the oviductal epithelial cells in female mice results in excess protease activity and increased expression of antimicrobial peptides such as defensins. These changes, due to a lack of ESR1 in the oviduct, dampen the plasma membrane integrity of the embryos and ultimately cause embryonic death before the 2-cell stage (Winuthayanon et al 2015). The study demonstrated that the epithelial ESR1 is required to suppress innate immune systems (Fig.…”
Section: Figurementioning
confidence: 97%
“…This elevated protease activity caused premature degradation of the zona pellucida (ZP) and embryo lysis and wild-type embryos transferred into cKO oviduct failed to develop normally unless rescued by concomitant transfer of protease inhibitors. It was concluded that oestrogen-epithelial receptor α is necessary to suppress oviductal protease activity, which is required for a successful fertilization and preimplantation embryo development (Winuthayanon et al 2015). Epithelial cells also play a role in the transport of the oocyte to the site of fertilization; whereas, during early embryo development, they contribute to creating an optimal environment.…”
Section: Epithelial Cellsmentioning
confidence: 99%